Obraz Boga w teologii Josepha Ratzingera/Benedykta XVI - Szymik, Jerzy (Śląskie Studia Historyczno-Teologiczne, 2011)
According to Ratzinger/Benedict XVI, the question concerning image of God is both hermeneutic and substantive one: a question about God Himself and the way we can get to know Him, express Him and convey. Thus, it constitutes an initial question of theology. Our current Pope calls for an adequately great image of God (free of any reductionisms) and christocentrically strengthened (Christ is the first and only faithful image of God and His similarity to God - kenosis and cross – is God’s similarity to a man). Paradox, as a verbal tool used to describe the very nature of God, corresponds to the paradoxical character of revelation itself. By revealing Himself, God transcends limitations of human logic and unites in Himself all that was separated by a sin. Maintaining this notion in theology also determines an ethical way of a man, who was created as God’s likeness and it reveals the whole truth about him.